Valuation of Vinhomes' company - Pham, Huynh Duc; Sieber, Patrik, 1977-; Kopkáně, Heřman; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2022)
The company value is essential information for owners and investors. They would like to know the present value to see if it is undervalued or overvalued compared to the market value. The market value accounting for market perceptions sometimes does not tell everything about that company. The objective of this thesis is to determine the value of Vinhomes, a well-known property developer in Vietnam, and its stock price as of December 31st, 2021, using the DCF valuation. The strategic analysis is analyzed to better assess Vinhomes’ current position and its potential in the future. The valuation results in an estimated share price of 105,836 VND, a bit higher than the market price (82,000 VND) on the last day of 2021.
Vedoucí práce: Patrik Sieber
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: business administration/corporate finance and management [obor bakal. práce]; bakalářské práce; bachelor's theses